A Feasibility study on the establishment of a one-stop shop for home repairs, maintenance, and minor renovations services - Agbay, Michael; Bacallan, Almer; Enderez, Anatolio; Sarmiento, Wilburt (Diliman, Quezon City College of Engineering, 2004)
The feasibility of establishing a one-stop shop for home repairs, maintenance, and minor renovations in Metro Manila was evaluated through the analysis of four major considerations: commercial, technical, financial, and socio-economic feasibility. The marketing feasibility study was achieved through the collection and analysis of secondary data from relevant sources such as statistical publications and websites, as well as a primary data from surveys conducted in homes throughout Metro Manila. The analysis of the marketing information indicated the presence of a very big market, with annual expenditures, specifically on home repair and maintenance, of 3.35 billion on 2001 alone, 2.8 billion attributed to AB Classes expenditure. The study also indicated a strong market growth growing more than 10% every year. The technical feasibility study was achieved by the exploration of all necessary inputs to the startup of the company, namely: the facilities, tool and equipment, vehicles, working materials, and labor. THe training of workers is based on the training guidelines set by the Technical Education and Skills Development Authority (TESDA). Two headquarters, one training facility, 109 workers, P1.7M worth of equipment, and 8 pickups are required in order to serve 1% of the indexed 2001 market on its first year. The headquarters are located in Commonwealth, Quezon City and in San Antonio, Makati; and the training facility is located in Taguig where it is closest to an urban poor community. The financial feasibility study was achieved by determining the capitalization requirements to serve 1% of the indexed 2001 market, a capacity level determined by considering capitalization and logistical constraints and financial goals, then factoring associated Revenues and Expenditures associated with that capacity. It was found that the financial profile of the company is very promising with an ROI or 93% and a payback of 1.2 years. The project's startup cost is approximately P8 million. The financial statements, income statements, cash flow statement and balance sheet were projected for a 5-year period. The social profitability study was achieved by determining the costs and benefits of implementing the project. The constraints, direct and indirect beneficiaries, externalities, and other benefits are valuated along with the costs. The social profitability of the study was evaluated using the Net Present Value, Internal Rate of Return, and the Benefit/Cost Ratio. The tests all yielded positive results. Thus, establishing a one-stop shop for home repairs, maintenance, and minor renovations in Metro Manila is proven to be feasible and profitable venture.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Casa De Casa, Inc; Dwellings--Maintenace and repair; Participatory monitoring and evaluation (Project management)